2012
DOI: 10.1063/1.4767772
|View full text |Cite
|
Sign up to set email alerts
|

A combined crossed-beam and theoretical study of the reaction dynamics of O(3P) + C2H3 → C2H2 + OH: Analysis of the nascent OH products with the preferential population of the Π(A′) component

Abstract: The gas-phase reaction dynamics of ground-state atomic oxygen [O((3)P) from the photo-dissociation of NO(2)] with vinyl radicals [C(2)H(3) from the supersonic flash pyrolysis of vinyl iodide, C(2)H(3)I] has been investigated using a combination of high-resolution laser-induced fluorescence spectroscopy in a crossed-beam configuration and ab initio calculations. Unlike the previous gas-phase bulk kinetic experiments by Baulch et al. [J. Phys. Chem. Ref. Data 34, 757 (2005)], a new exothermic channel of O((3)P) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 49 publications
4
10
0
Order By: Relevance
“…The result also shows good agreement with the other theoretical investigations of the reverse reaction of C 2 H 2 + OH, where as the OH radical approaches C 2 H 2 , the association complex exists as the prereaction association complex along the entrance channel. 9 Similar weakly bound adducts were reported in the authors' studies on the formation of OH in the reactions of O( 3 P) with ethyl and iso-propyl radicals. 7,8 A competing but straightforward process responsible for reaction channel 10 is the direct H-atom abstraction from the CH 2 side through the collinear geometry.…”
Section: The Journal Of Physical Chemistry Asupporting
confidence: 75%
See 1 more Smart Citation
“…The result also shows good agreement with the other theoretical investigations of the reverse reaction of C 2 H 2 + OH, where as the OH radical approaches C 2 H 2 , the association complex exists as the prereaction association complex along the entrance channel. 9 Similar weakly bound adducts were reported in the authors' studies on the formation of OH in the reactions of O( 3 P) with ethyl and iso-propyl radicals. 7,8 A competing but straightforward process responsible for reaction channel 10 is the direct H-atom abstraction from the CH 2 side through the collinear geometry.…”
Section: The Journal Of Physical Chemistry Asupporting
confidence: 75%
“…This investigation was carried out as part of continuing efforts to deduce the general principles that explain the mechanistic and dynamic traits of atom-radical reactions. In recent years, the authors have reported gas-phase crossed-beam studies of the reaction dynamics of O­( 3 P) with saturated hydrocarbon radicals such as methyl (CH 3 ), ethyl (C 2 H 5 ), and t -butyl ( t -C 4 H 9 ) and unsaturated π-conjugated hydrocarbon radicals such as allyl (C 3 H 5 ) and propargyl (C 3 H 3 ). A supersonic flash pyrolysis source was adopted to produce clean, jet-cooled radical beams without experiencing recombination and/or secondary dissociation. By means of ab initio simulations and statistical calculations, these experiments revealed that the atom-radical reactions followed microscopic mechanisms with unusual dynamic features.…”
Section: Introductionmentioning
confidence: 99%
“…After considering the barrier height and reaction exothermicity along the reaction coordinate, the title reaction is, in fact, predicted to be a major channel, which is consistent with the gas-phase kinetic experiments. [5][6][7][8][9][10][11] Statistical Analyses and Reaction Dynamics. The partitioning of the energy into the H products and the microscopic kinetic rate constants were derived using the aforementioned ab initio calculations.…”
Section: Discussionmentioning
confidence: 99%
“…The crossed-beam apparatus used in this study was made in-house and has been described in detail elsewhere. 3,[5][6][7][8][9][10][11] In brief, a pulsed O( 3 P) radical beam was produced by irradiating 2 atm of He (ultra-high-purity helium: 99.999%) seeded with 12% NO 2 (99.5%, MG Industries) with 30 mJ pulses from a 355 nm Nd:YAG laser beam (Continuum Surelite II-10) near the throat of the supersonic expansion. A second C 2 H 5 radical beam was prepared by supersonic flash pyrolysis of the precursor, azoethane (C 2 H 5 -N=N-C 2 H 5 ), synthesized using the method of Renaud and Leitch.…”
Section: Experimental and Ab Inito Calculationsmentioning
confidence: 99%
See 1 more Smart Citation